Best practice for perioperative management of patients with cytoreductive surgery and HIPEC. Issue 6 (June 2017) - Raspé, C.; Flöther, L.; Schneider, R.; Bucher, M.; Piso, P.
Abstract: Due to the significantly improved outcome and quality of life of patients with different tumor entities after cytoreductive surgery (CRS) and HIPEC, there is an increasing number of centers performing CRS and HIPEC procedures. As this procedure is technically challenging with potential high morbidity and mortality, respectively, institutional experience also in the anesthetic and intensive care departments is essential for optimal treatment and prevention of adverse events. Clinical pathways have to be developed to achieve also good results in more comorbid patients with border line indications and extensive surgical procedures. The anesthesiologist has deal with relevant fluid, blood and protein losses, increased intraabdominal pressure, systemic hypo-/hyperthermia, and increased metabolic rate in patients undergoing cytoreductive surgery with HIPEC. It is of utmost importance to maintain or restore an adequate volume by aggressive substitution of intravenous fluids, which counteracts the increased fluid loss and venous capacitance during this procedure. Supplementary thoracic epidural analgesia, non-invasive ventilation, and physiotherapy are recommended to guarantee adequate pain therapy and postoperative extubation as well as fast-track concepts. Advanced hemodynamic monitoring is essential to help the anesthesiologist picking up information about the real-time fluid status of the patient. Preoperative preconditioning is mandatory in patients scheduled for HIPEC surgery and will result in improved outcome. Postoperatively, volume status optimization, early nutritional support, sufficient anticoagulation, and point of care coagulation management are essential. This is an extensive update on all relevant topics for anesthetists and intensivists dealing with CRS and HIPEC.